Pérdida dental prematura y sus principales causas en los y las estudiantes de la Universidad Nacional de Loja en la modalidad de estudios presencial en edades comprendidas de 18 a 30 años en el periodo mayo julio de 2014. - Silva Chase, María José (2014)
At the present time the buccal diseases are considered like the more common chronic pathologies of the world, with a high prevalence, great impact in the individuals and the community, affecting the quality of life and general health being an important problem of public health. The present investigation tries to identify the main causes that cause lost dental the premature one in the students of the National University in the actual modality of studies, in the identified cases it was come to determine the main causes that cause lost dental the premature one. The obtained results were collected by means of the application the odontológica clinical history the same one that allowed me to state that almost all the examined group presents some lost dental or by traumatisms. within the main found causes were dental decay and traumatisms, the general population in which the study was made was of 894 students of who it was that a 45% (398 students) present/display lost dental, being that a 76% present/display lost dental because of decay, whereas a 24% present/display lost by traumatisms. Keywords: Tooth Loss, Dental Caries, Trauma.